PERAN PEMUKA MASYARAKAT DALAM MENYELESAIKAN KONFLIK DI GUNUNG JATI KECAMATAN KENDARI BARAT - Lilin Handriani Bahtiar, dan Hj. Ratna Supiyah (Jurnal Neo Societal, 2017)
Problems in Research It Is What Community Leaders Role in Resolving Conflict In Gunung Jati subdistrict of West Kendari. This study aims to describe the role of Community Leaders, Local Government And Public Institutions to Address Conflict Inter-group in the Village Gunung Jati And Jati Mekar Village Kendari. This research Located In Village Gunung Jati And Mekar Jati village. This research Implemented With How to Collect Data Through Observation Form Field Research And Depth interview. Results of this study indicate that role of the Government of the District, Public Agencies, as well as The Police's been running as it should be complied with Tasks and Functions of Each For The First In Decision Making and Policy Although Handling Government is still quite weak, Will but in this case the Local Government Neutral Position already without distinction to Each Lain.Untuk resolving the conflict in the Village Gunung Jati And Jati Mekar Village, Village Government And Community Leaders To mediation order for this problem to Achieve Peace Point. In It Is What have adequate Local Government Role As a facilitator Has Successfully Resolving Conflicts With Other Words misconceptions Interagency Youth Groups Such Bite by Bite Can Open. Such Obtained from the Research Several efforts made by the Government, Good That The Police And Community Leaders Work Together In Addressing Conflict Between Youth And Village Sub Gunung Jati Mekar Jati. Thanks to Hard Work and Cooperation Them, Now In Two village Such situation can be said Safe While Time.